Optimization Of Fortified Parboiling Process Of White Rice With Clitoria Ternatea Flowers Extract And Its Characterization Of Physicochemical, Cooking Properties And Storage Stability - Ramli, Muhammad Ezzudin (2019)
Clitoria ternatea flower extract is commonly used in making blue rice of popular Malay delicacy “Nasi Kerabu”. A fortified parboil process was developed. Flavonoid fortification and blue coloration of white rice was developed by parboiling process using the Clitoria ternatea (CT) flower extract. The physicochemical, cooking properties and storage stability of the fortified rice were studied and compared with raw and white parboiled rice as control. In Phase 1, the fortification method was introduced during soaking of white rice with CT extract (1:100 w/v) to replace water prior to steaming and drying. The fortified parboiling process of three different varieties of rice namely MRQ 74, MRQ 76 and glutinous rice was optimized using full factorial design with two processing parameters: soaking temperatures (50, 60, and 70°C) and soaking time (10, 20, and 30 minutes) to obtain maximum total flavonoid content (TFC) of the fortified rice.